2021
DOI: 10.33594/000000337
|View full text |Cite
|
Sign up to set email alerts
|

KCNQ5 Potassium Channel Activation Underlies Vasodilation by Tea

Abstract: BACKGROUND/AIMS: Tea, produced from the evergreen Camellia sinensis, has reported therapeutic properties against multiple pathologies, including hypertension. Although some studies validate the health benefits of tea, few have investigated the molecular mechanisms of action. The KCNQ5 voltage-gated potassium channel contributes to vascular smooth muscle tone and neuronal M-current regulation. METHODS: We applied electrophysiology, myography, mass spectrometry and in silico docking to determine effects and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…[ 27 ] We speculated that water‐soluble compounds present in green tea might affect these plasma membrane‐located K + channels. Catechin derivatives contained in green tea are known to regulate ion transport activities of Shaker ‐type K + channels [ 20 , 21 , 22 ] by binding to the gap site between S4 and S5, [ 28 ] and Ca 2+ channels. [ 29 , 30 ] Prior to this test on plant channels, we tested whether green tea directly affects the activity of animal K + channels using two‐electrode voltage clamp recordings of Xenopus oocytes ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 27 ] We speculated that water‐soluble compounds present in green tea might affect these plasma membrane‐located K + channels. Catechin derivatives contained in green tea are known to regulate ion transport activities of Shaker ‐type K + channels [ 20 , 21 , 22 ] by binding to the gap site between S4 and S5, [ 28 ] and Ca 2+ channels. [ 29 , 30 ] Prior to this test on plant channels, we tested whether green tea directly affects the activity of animal K + channels using two‐electrode voltage clamp recordings of Xenopus oocytes ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that catechins had some affinity to Shaker ‐type ion channels, which was consistent with a previous report. [ 28 ] We performed the same measurement on Shaker ‐type K + channels, KAT1 and KAT2, which function in the plasma membrane of Arabidopsis guard cells [ 34 ] (Figure 2 ). The addition of green tea to the bath buffer decreased KAT1 and KAT2‐mediated currents by more than 40%, compared to the buffer without green tea (Figure 2A,B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One example is the ester of epigallocatechin and gallic acid, ( −)-Epigallocatechin-3-Gallate (EGCG), the most bioactive polyphenol found in green tea extract. EGCG significantly increased mRNA expression of the key autophagy adaptor proteins NDP52 and p62 and enhanced the clearance of AD-relevant phosphorylated tau species in primary neurons [ 145 ], as well as improving cerebrovascular tone [ 146 ]. EGCG also activated autophagic pathways by inducing Sirt1, exerting protective effects against human prion protein-induced neurotoxicity [ 69 ].…”
Section: Boosting Energy To Rescue Ad Pathologymentioning
confidence: 99%